BRAIN DUMP ACTIVITIES TO OVERCOME STUDENT’S INTRINSIC COGNITIVE LOAD IN REPRODUCTIVE SYSTEMS ONLINE LEARNING - Handayanie, Yunni; Rahmat, Adi; Priyandoko, Didik (Jurnal Pengajaran MIPA, 2021)
This study aimed to overcome the intrinsic cognitive load in reproductive system learning by providing brain dump activities. Quasi-experimental was used in this study by using the post-test only control group design. A total of 41 students of the XI class was involved in this study which were divided into two groups, namely the treatment group and the control group. Learning was carried out in two meetings which are asynchronously and synchronously learning in two groups. Brain dump activities were carried out by asking four questions, namely: what you are thinking about, what you will do, what are the three main priorities that will be done, and what you are grateful for. Intrinsic cognitive load was measured using a subjective rating scale with a scale of 1 - 8 at each meeting. In treatment group, intrinsic cognitive load was lower than the control group. The results of the mean difference test in intrinsic cognitive load showed a significant difference (sig. = 0.0190.050) between the treatment group and the control group. These results illustrate that in reproductive system learning using brain dump activities can overcome students' intrinsic cognitive load.